Comparative investigation of 15 Level and 17 level cascaded h-bridge MLI with cross h-bridge MLI fed permanent magnet synchronous motor - J. Srinivas Rao; Suresh Kumar Tummala; Narasimha Raju Kuthuri (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Multilevel inverters offers eminent solutions to high voltage high power applications due to the association of several devices in a series configuration. In this paper, a comparative investigation of both 15 and 17 level cascaded h-bridge multi level inverter with cross h-bridge fed permanent magnet synchronous motor are presented by appropriate simulations and mathematical analysis. Comparative analysis includes Inverter output voltage and current, number of switching devices, stator current and speed of PMSM and total harmonic distortion levels. Limitation of several switching devices, which can afford high voltage in the inverter is the major problems raised in this study. The advantage of this analysis is to figure out the appropriate inverter that can be used for real time application by considering the factors via. Harmonic distortion, output voltage, current, number of switching devices etc. Validation of the analysis is processed through matlab/simulink platform.